Sabri Orman’s Inquiry into Social Justice Regarding al Ghazali’s Adalet-I Ijtimâ’iye Doctrine - Rahmi Deniz Özbay; Hassan Syed (İstanbul Üniversitesi Sosyoloji Dergisi)
Contemporary economics scholars are increasingly trying to understand the interplay between social justice and economics, with Adam Smith’s idea of the rational agent behaving according to the economic tides, detached from any semblance of justice, morality, or fairness being questioned. The contemporary socioeconomic complexities exacerbated by overexploitation of the Earth’s limited natural resources have exposed environmental agendas as a current priority. The Islamic Golden Age gave birth to a documented socioeconomic and sociopolitical literature spanning over 500 years, while mankind faces serious socioeconomic and environmental challenges that call for a unified effort to find tangible solutions, with socioeconomic justice being crucial for this to occur. Al Khaldun’s Muqaddimah [Prolegomenon] and al Ghazali’s Iḥyā′ ‘Ulūm al-Dīn [Revival of the Religious Sciences] shed a unique light on social justice, with both scholars being strong advocates of justice as a basic tenet of a prosperous society. However, the concept of social justice is normally attributed to contemporary Western democratic thought. Sabri Orman’s analysis of al Ghazali’s doctrine adalet-i ijtimâ’iye [on social justice] provides an alternative view with some solid scholarly arguments. This paper presents some of the key conclusions from Sabri Orman’s work on Ghazali’s doctrine adalet-i ijtimâ’iye and also examines some of the misconceptions about al Ghazali’s doctrine on social justice.